A STUDY ON THE READER’S REVIEW TOWARDS THE ENGLISH USAGE OF “THE HINDU” - C., R.Marcelin Vasantha; V., Manimozhi (International Journal of Psychosocial Rehabilitation, 2020)
To find out the opinion of readers on “The English usage of The Hindu.". “The press is the fourth pillar of democracy.”.Even though it flashes the day today affairs or events, by the way it focuses the issue through the usage of the language, it may give a totally different shade to the content. Newspapers have an important role to play, and they have a strong social responsibility. And at the same time, they have pressure to hold the readers in order to maintain or increase the circulation rate. Way of witting is an important factor to keep the target audience in its custody.